Exploring the Environmental Justice Implications of Hurricane Harvey Flooding in Greater Houston, Texas. - Chakraborty, Jayajit; Collins, Timothy W.; Grineski, Sara E. (American Journal of Public Health, 2019)
Objectives. To assess the environmental justice implications of flooding from Hurricane Harvey in Greater Houston, Texas, we analyzed whether the areal extent of flooding was distributed inequitably with respect to race, ethnicity, and socioeconomic status, after controlling for relevant explanatory factors.Methods. Our study integrated cartographic information from Harvey’s Inundation Footprint, developed by the US Federal Emergency Management Agency, with sociodemographic data from the 2012–2016 American Community Survey. Statistical analyses were based on bivariate correlations and multivariate generalized estimating equations.Results. The areal extent of Harvey-induced flooding was significantly greater in neighborhoods with a higher proportion of non-Hispanic Black and socioeconomically deprived residents after we controlled for contextual factors and clustering.Conclusions. Results provide evidence of racial/ethnic and socioeconomic injustices in the distribution of flooding and represent an importa...

Environmental injustice and flood risk: a conceptual model and case comparison of metropolitan Miami and Houston, USA - Collins, Timothy W.; Grineski, Sara E.; Chakraborty, Jayajit (Regional Environmental Change, 2018)

Social and spatial inequities in exposure to flood risk in Miami, Florida - Chakraborty, Jayajit; Collins, Timothy W.; Montgomery, Marilyn; Grineski, Sara E. (Natural Hazards Review, 2014)
AbstractAlthough environmental justice (EJ) research in the United States has traditionally focused on technological hazards such as air pollution or hazardous waste, the adverse and unequal impacts of Hurricane Katrina have prompted researchers to examine the EJ implications of natural events such as hurricanes and floods. This paper contributes to this emerging literature on EJ and social vulnerability to natural hazards by analyzing racial/ethnic and socioeconomic inequities in the distribution of flood risk exposure in the Miami Metropolitan Statistical Area (MSA), Florida—one of the most hurricane-prone areas in the world and one of the most ethnically and socioeconomically diverse MSAs in the United States. Although previous studies have relied exclusively on the 100-year floodplain to assess the spatial extent of flood exposure, this study makes a systematic distinction between different types of flood zones on the basis of both the probability (100-year versus 500-year versus low/no risk) of flood...